2023
DOI: 10.3389/fphar.2023.1158222
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual-specific cardiotoxicity responses induced by tyrosine kinase inhibitors

Abstract: Introduction: Tyrosine kinase inhibitor drugs (TKIs) are highly effective cancer drugs, yet many TKIs are associated with various forms of cardiotoxicity. The mechanisms underlying these drug-induced adverse events remain poorly understood. We studied mechanisms of TKI-induced cardiotoxicity by integrating several complementary approaches, including comprehensive transcriptomics, mechanistic mathematical modeling, and physiological assays in cultured human cardiac myocytes.Methods: Induced pluripotent stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…83−85 In addition, some studies integrated transcriptomics with disease-associated genetic variants and mechanistic models to generate experimentally testable hypotheses of adverse event risk. 27,86 Collectively, these studies demonstrate that transcriptional profiles in human cardiomyocytes can be used to derive mechanism-based drug signatures, information that could be useful to predict the cardiotoxic potential of existing and new chemicals. Our study provides additional information in terms of the number and diversity of chemicals.…”
Section: ■ Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…83−85 In addition, some studies integrated transcriptomics with disease-associated genetic variants and mechanistic models to generate experimentally testable hypotheses of adverse event risk. 27,86 Collectively, these studies demonstrate that transcriptional profiles in human cardiomyocytes can be used to derive mechanism-based drug signatures, information that could be useful to predict the cardiotoxic potential of existing and new chemicals. Our study provides additional information in terms of the number and diversity of chemicals.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Transcriptomic effects of various drugs on iPSC-derived cardiomyocytes have been explored by several groups. ,,, These studies identified molecular mechanisms underlying adverse effects of both individual cardiotoxic compounds and entire drug classes. In addition, some studies integrated transcriptomics with disease-associated genetic variants and mechanistic models to generate experimentally testable hypotheses of adverse event risk. , Collectively, these studies demonstrate that transcriptional profiles in human cardiomyocytes can be used to derive mechanism-based drug signatures, information that could be useful to predict the cardiotoxic potential of existing and new chemicals. Our study provides additional information in terms of the number and diversity of chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this expands the input space and might be unsuitable for solving the inverse problem when only AP data are used. Moreover, drugs that are applied over a longer period of time can also cause modifications of the maximum conductances through changes in gene expression ( Shim et al, 2023 ). This requires attention to avoid misinterpretations of found blocking or enhancement effects, for example by estimating the control maximum conductances again after a washout procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although most models that capture biochemical SCPs use a pathways framework, biophysical models can also capture changes in gene expression to predict responses to perturbation. In a recent study using cardiomyocytes differentiated from healthy human subjects, gene expression changes induced by tyrosine kinase inhibitor drugs that are effective cancer therapeutics was used to develop computational models that predict arrhythmogenic responses to cancer drug therapy in individuals ( Shim et al, 2023 ). Changes in levels of gene expression of different channel proteins by drugs were scaled and incorporated as changes in level of channel proteins into a multicompartment ODE model of cardiomyocyte action potential and contractility.…”
Section: Predicting Cardiomyocyte Electrophysiology and Contractility...mentioning
confidence: 99%